An Analysis of the Use of EE Structural Assistance to Improve the Quality of Business Environment in the Moravia-Silesian Region - Černý, Igor; Rolčíková, Markéta; Krčmarská, Lucie; Böhm, Richard (GeoScience Engineering, 2013)
The article deals with business environment in the moravia-silesian region, which is very various, dynamic and complex. It is influenced by many factors, which can have positive or negative impacts on corporations. The objective of the article is to determine the structural assistance from the operational programmes in the programming period 2007 – 2013, which can reinforce the factors influencing this business environment, and this way improve the quality of this environment, and to evaluate mutual relationships among the operational programmes and the factors. The article defines these factors, the structural assistance of the european union, finds and analyses their mutual relationships.